Revitalizing Destination Social Responsibility through Regenerative Tourism: A Case Study of Penglipuran Village, Bali - I Putu Andre Adi Putra Pratama; I Gede Gian Saputra; I Gusti Ngurah Oka Widjaya; Putu Ade Wijana (Yayasan Ghalih Pelopor Pendidikan, 2026)
This study investigates how regenerative tourism can revitalize Destination Social Responsibility within a mature and economically successful community-based destination. Using a qualitative case study approach, data were generated through a Focus Group Discussion with ten key stakeholders representing customary leadership, tourism governance, academic expertise, and youth perspectives. The analysis reveals that Penglipuran’s long-standing commitment to Tri Hita Karana constitutes an Organic DSR model that predates contemporary responsibility frameworks. However, this foundation is increasingly undermined by an economic euphoria that erodes collective governance and by an intergenerational gap in cultural knowledge transmission. These dynamics reflect an erosion by the success paradox that remains insufficiently addressed in existing DSR scholarship. The findings show that regenerative tourism offers a practical pathway to restore Organic DSR by reorienting destination success toward measurable cultural, social, and ecological regeneration. The study’s single case focus suggests the need for comparative and longitudinal research.